ELUSIDASI STRUKTUR PRODUK SAMPING DARI HASIL SINTESIS SENYAWA THPGV-1 DAN UJI ANTIINFLAMASI SENYAWA THPGV-1 - , Fransiska Ayuningtyas Widyastani, Dr. Ritmaleni, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
THPGV-1 has been sucesfully synthesised by using the hydrogenation reaction methode where Pd/C was used as catalyst, hydrogen gas as source of hydrogen and PGV-1 as starting material. The reaction was carried out at room temperature for two hours and yielded THPGV-1 in 18% and three others side products. The aim of this research was to elucidate this sructure of side products and to investigate the anti-inflamatory activity of THPGV-1. Structure elucidations were carried out by using the spectroscopic method (1H-NMR, 2D-NMR, IR and MS) and anti-inflamatory activity was performed by the method of carragenan-induced footpad edema. Anti-inflamtory activity THPGV-1 admnistered orally to mice a moment before carragenan injection. THPGV-1 was comparable to PGV-1. Swelling measurements performed every 30 minutes for 6 hours using calipers. The side productsâ structures are found 1,3-bis-(4'-hydroxy-3',5'-dimethyl) benzylcyclopentane (compound A) in 30.33% yield as white crystalline powder with MW= 338 g/mol, 2,5-bis-(4Ì-hydroxy-3Ì,5Ì-dimethyl)benzylcyclopentanol (compound B) in 7.04% yield as white crystalline powder with MW= 354 g/mol and and compound C is an isomer of compound B in 15.38% yield as white crystalline powder with MW= 354 g/mol. Anti-inflammatory activity can be seen in the results of that test in different dossage are 60,80,100,120 mg /Kg body weight with anti-inflamation zone percentage respectively 69.97 Â± 1.71%